Hubungan Kedisiplinan Pemakaian Alat Pelindung Mata dengan Kelelahan Mata pada Pekerja Las di Sukawati - Ni Made Maharani Dwimarthaswari; A.A. Sri Agung Aryastuti; Ni Nyoman Sunariasih (Aesculapius Medical Journal, 2024)
[Correlation Between the Discipline of Using Eye Protective Equipment and Eye Fatigue in Welding Workers in Sukawati District] Welding is a process of joining several metals to form an effective whole. Workers in welding industries can be exposed to high intensity of light welding radiation, which can have an impact on eye health, one of which causes eyestrain. According to several studies, the use of eye protective equipment (APM), such as welding goggles, can reduce eyestrain; however, the awareness of welders in using APM is relatively low. The aims of this study was to determine the relationship of the eyestrain of welding workers in Sukawati and their awareness of wearing APM. The sampling technique employed in this study was total enumeration, encompassing a total cohort of 105 individuals. Data was collected using a Visual Fatigue Index (VFI) questionnaire by looking at the symptoms of welders’ eyestrain. Relationships between variables were tested by data analysis using bivariate analysis through the computerized system of the SPSS program. The findings of this investigation reveal that a significant proportion of welders fall under the age category of >31 years (53.3%), have work shifts lasting >6 hours (64.8%), possess job tenure exceeding 3 years (61.9%), and abstain from utilizing APM (65.7%); eye fatigue is predominantly experienced by the participants (67.6%). The bivariate analysis outcomes suggest a correlation between the conscientiousness of welders in adopting APM and their susceptibility to eye fatigue, with a prevalence ratio of 4.770 (p = 0.001; CI: 2.445 - 9.305). It can be inferred that the diligence in employing APM is linked to the incidence of eye fatigue in welders within Sukawati District. Consequently, it is recommended that welders take periodic breaks using the 20:20:20 method to alleviate eye strain.